Comparison of Nausea and Vomiting Associated With Amino Acid Formulations Coinfused With Peptide Receptor Radionuclide Therapy: Commercial Parenteral Nutrition Formulas Versus Compounded Arginine/Lysine. Issue 4 (April 2021) - Al-Toubah, Taymeyah; Sikaria, Dhiraj; Jesurajan, Jose; Bottiglieri, Salvatore; Smith, Johnna; Pellé, Eleonora; Hutchinson, Tai; Strosberg, Jonathan; El-Haddad, Ghassan
Abstract : Objectives: Positively charged amino acids (AA) such as arginine/lysine are coinfused with radiolabeled somatostatin analogs to reduce rates of nephrotoxicity. In the phase 3 NETTER-1 trial, commercial AA formulations were used in association with 177 Lu–DOTA-0-Tyr3-Octreotate (DOTATATE). These formulations were also used in an early-access program (EAP) before regulatory approval of 177 Lu-DOTATATE. Our program transitioned to compounded L-arginine 2.5%/L-lysine 2.5% in 0.9% NaCl after commercial approval of 177 Lu-DOTATATE. We sought to compare rates of nausea/vomiting with arginine/lysine versus commercial parenteral AA formulations. Methods: Rates of nausea/vomiting of all 20 EAP patients who received commercial AAs (15% Clinisol) were compared with the first 29 patients to receive 177 Lu-DOTATATE after commercial approval and coinfused with arginine/lysine. Other parameters reviewed included infusion rates, need for PRN nausea medications, and other toxicities. Results: Seventeen percent of patients who received compounded arginine/lysine experienced nausea, compared with 100% of patients in the EAP group ( P < 0.0001). Infusion-related reactions occurred in 3% of the arginine/lysine cohort versus 35% in the EAP group. Infusion durations were substantially shorter in the arginine/lysine cohort (reduced by 61%). Conclusions: Coinfusions of arginine/lysine with radiolabeled somatostatin analogs result in substantially lower rates of nausea/vomiting compared with commercial AA formulations designed for parenteral nutrition.